Tillage and seeding strategies for wheat optimizing production in harvested rice fields with high soil moisture - Jinfeng Ding (Nature Portfolio, 2021)
Abstract Suitable tillage and seeding strategies for wheat can be used to combat excessive residues and poor soil conditions in harvested rice fields. This study investigated the effects of different tillage (zero tillage and rotary tillage) and seeding methods on wheat growth, grain yield, nitrogen (N) uptake and utilization, and economic benefit when the soil moisture was high during the tillage and seeding practices. In 2016–2017, three seeders were tested: SM1-1, SM2, and SM3; in 2017–2018, four seeders were tested: SM1-2, SM2, SM3, and SM4. Although the soil moisture was different between years, zero tillage could be used to reduce the sowing depth, which facilitated early-phase wheat growth and N uptake compared with rotary tillage, resulting in higher grain yield, NUpE, and net return. In 2016–2017 (high wet soil), a small-size seeder (SM1-1) with sowing near the soil surface facilitated higher grain yield, NUpE, and net returns compared with the other seeders; in 2017–2018 (low wet soil), medium-size seeders (SM3 and SM4) were more suitable than small-size seeders (SM1-2 and SM2). In both years, the seeders that performed the best mainly improved the spike numbers while increasing N uptake, especially after anthesis. Zero tillage lowered input costs, but small-size seeders did not reduce costs due to the higher labor costs associated with their low working efficiency. Improving net returns depends largely on increasing yield. In conclusion, zero tillage is recommended for wheat production in harvested rice fields with a high soil moisture content, but the suitable seeding method needs to be confirmed according to the soil moisture content.